2014
DOI: 10.3109/0142159x.2014.947928
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lapses in academic integrity in two Pakistani medical colleges

Abstract: There are significant issues related to academic integrity in Pakistani medical schools that require remedy. The Dundee Polyprofessional Inventory-1 as customized for use in Pakistan is a useful tool to measure professionalism lapses related to academic integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Developing countries are also trying to create awareness about the importance of the medical ethics. For example, the Pakistan Medical and Dental Council encourages that a physician should always ensure they maintain the highest standards of professional conduct, conform to principles of justice and honesty, and recommends that all dental and medical institutions and colleges include medical ethics in their curricula and this is extended to practicing health workers 20. Academic integrity can also be instilled through effective student-teacher relationships as shown by a study done at the University of Punjab 21,22.…”
Section: Discussionmentioning
confidence: 99%
“…Developing countries are also trying to create awareness about the importance of the medical ethics. For example, the Pakistan Medical and Dental Council encourages that a physician should always ensure they maintain the highest standards of professional conduct, conform to principles of justice and honesty, and recommends that all dental and medical institutions and colleges include medical ethics in their curricula and this is extended to practicing health workers 20. Academic integrity can also be instilled through effective student-teacher relationships as shown by a study done at the University of Punjab 21,22.…”
Section: Discussionmentioning
confidence: 99%
“…The results were compared to previous published studies using the Dundee Polyprofessionalism Inventory in three overseas medical schools comprising Egyptian (n=219), 13 Saudi Arabian (n=96), 14 and Pakistani (n=480) 15 medical students.…”
Section: Data Collectionmentioning
confidence: 97%
“…Equally, borrowing other's work, reusing other's words or ideas intentionally passing others' work off as your own was viewed as problematic. Some of the literature we identified related to academic integrity (e.g., Abdel-Hadi, 2017;Abdulghani et al, 2018;Abdulrahman, Alsalehi, Husain, Nair, & Carrick, 2017;Shukr & Roff, 2015) separates plagiarism and cheating, other scholars believe that cheating and plagiarism cannot be separated and explore the two interrelated academic breaches in their contexts (e.g., Abou-Zeid, 2016;Cinali, 2016;Mohanty, 2016;Orim, 2016).…”
Section: Key Topics Related To the Academic Integrity Concept And Culmentioning
confidence: 99%
“…We found eight studies that explored cheating as a stand-alone academic integrity breach among students and academics. Four studies explore the prevalence of cheating behaviours among students and found that this type of academic dishonesty remains extremely common (Abdel-Hadi, 2017; Abdulghani et al, 2018;Abdulrahman, Alsalehi, Husain, Nair, & Carrick, 2017;Shukr & Roff, 2015). Two studies focus on finding solutions for student cheating by examining the potential of drawing on Islam to combat cheating.…”
Section: Key Topics Related To the Academic Integrity Concept And Culmentioning
confidence: 99%
See 1 more Smart Citation